Faktor-Faktor yang Berhubungan dengan Kecemasan Pegawai Kantor Kesehatan Pelabuhan Terkait Coronavirus Disease 2019 (Covid-19) - Arisca Dewi Safitri; Ari Udijono; Nissa Kusariana; Lintang Dian Saraswati (Media Penelitian dan Pengembangan Kesehatan, 2022)
The number of positively confirmed cases of COVID-19 is influenced by several factors, both internal and external factors. The high number of cases and the number of health workers infected with COVID-19 make employees who handle COVID-19 at the Port Health Office (KKP) experience psychological disorders. There has been no specific report on the exposure status of COVID-19 for employees who serve in high-risk places, such as KKP. This research article aims to find out the factors related to the anxiety levels of port health office employees related to Coronavirus Disease 2019 (COVID-19). This research is observational cross sectional design analytics. The research population is the State Civil Apparatus at Port Health Offices throughout Indonesia. Respondents who met the criteria were 533 employees. Simple random sampling technique. The study data was collected using a modified Zung Self-rating Anxiety Scale (ZSAS) questionnaire. The data is collected online using google form. Using univariate and bivariate analysis using the Chi-Square test. From the results of bivariate analysis continued with multivariate analysis to find out the factors that affect the level of anxiety of KKP employees related to COVID-19. The results of the analysis of multiple logistic regressions on age, sex, health conditions, environment and availability of infrastructure facilities obtained factors that significantly affect the level of anxiety with α<0.05 are gender (α<0,000), environment (α<0.017), and health conditions (α<00,043). The sex factor had the strongest influence with the largest beta coefficient (0.154). Anxiety can have a negative impact on health workers who deal with COVID-19. It is recommended that the government facilitate more in mental or psychological maintenance, especially in health workers such as counseling services, mental health screening. Abstrak Banyaknya kasus terkonfirmasi positif COVID-19 dipengaruhi beberapa faktor, baik faktor internal maupun eksternal. Tingginya kasus dan banyaknya petugas kesehatan yang terinfeksi COVID-19 membuat pegawai yang menangani COVID-19 di Kantor Kesehatan Pelabuhan (KKP) mengalami gangguan psikologis. Belum ada laporan khusus mengenai status keterpaparan COVID-19 bagi pegawai yang bertugas di tempat berisiko tinggi, seperti KKP. Artikel penelitian ini bertujuan mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan pegawai kantor kesehatan pelabuhan terkait Coronavirus Disease 2019 (COVID-19). Penelitian ini adalah observasional analitik desain cross sectional. Populasi penelitian adalah Aparatur Sipil Negara di Kantor Kesehatan Pelabuhan di seluruh Indonesia. Responden yang memenuhi kriteria adalah 533 pegawai. Teknik sampling simple random sampling. Data penelitian dikumpulkan dengan menggunakan kuesioner Zung Self-rating Anxiety Scale (ZSAS) yang telah dimodifikasi. Data tersebut dikumpulkan dengan angket online menggunakan google form. Menggunakan analisis univariat dan bivariat menggunakan uji Chi-Square. Dari hasil analisis bivariat dilanjutkan dengan multivariat analisis untuk mengetahui faktor-faktor yang berpengaruh terhadap tingkat kecemasan pegawai KKP terkait COVID-19. Hasil analisis regresi logistik ganda terhadap usia, jenis kelamin, kondisi kesehatan, lingkungan dan ketersediaan sarana prasarana didapatkan faktor-faktor yang berpengaruh bermakna terhadap tingkat kecemasan dengan α<0,05 adalah jenis kelamin (α<0,000), lingkungan (α<0,017), dan kondisi kesehatan (α<0,043). Faktor jenis kelamin mempunyai pengaruh paling kuat dengan koefisien beta terbesar (0,154). Kecemasan dapat berdampak negatif pada tenaga kesehatan yang menangani COVID-19. Disarankan agar pemerintah lebih memfasilitasi dalam pemeliharaan mental atau psikologis khususnya pada tenaga kesehatan seperti pelayanan konseling, screening kesehatan mental.